Stationary oscillations in degenerated case - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 1996)
In the present paper, some remarks about stationary oscillations in degenerated case are presented. It is shown that these oscillations may exist, may be stable or unstable and they are represented by singular points of the response curve.